Larval description of Drusus bosnicus Klapálek 1899 (Trichoptera: Limnephilidae), with distributional, molecular and ecological features - Kučinić, Mladen; Previšić, Ana; Graf, Wolfram; Mihoci, Iva; Šoufek, Marin; Stanić-Koštroman, Svjetlana; Lelo, Suvad; Vitecek, Simon; Waringer, Johann (Zootaxa, 2015)
In this study we present morphological, molecular and ecological features of the last instar larvae of Drusus bosnicus with data about distribution of this species in Bosnia and Herzegovina. We also included  the most important diagnostic features enabling separation of larvae of D. bosnicus from larvae of the other European Drusinae and Trichoptera species.